Assistance in Making Biopores as a Groundwater Conservation Effort - M. Fikri Amrullah; Sriyanto; Achsin Baidowi (Educate: Journal of Community Service in Education, 2024)
ABSTRACT Engagement in community service with the theme of environmental conservation aims to increase public awareness of the importance of preserving the environment for sustainability. This activity is carried out through various implementation methods, such as counseling, practical exercises, training, and the creation of biopores. The project will be conducted in Sekaran Village, RT 02 RW 02, Gunungpati Sub-district, Semarang City. The approach will involve outreach and practical demonstrations, targeting the community in Dasa Wisma groups in RT 02 RW 02 Sekaran. Evaluation will be conducted to enhance the quality of future activities. The project has progressed smoothly and effectively, encompassing stages from socialization, implementation (biopore creation), to evaluation. During this initiative, 10 biopores were constructed at different locations within the RT 02 RW 02 Sekaran area. The enthusiasm of the community (Dasa Wisma group) in participating in this activity was remarkably high, evidenced by nearly 90% attendance of Dasa Wisma members and other community members outside this group. The project provided knowledge and skills to the community regarding environmental conservation methods, ecological restoration, and enhanced community involvement in preserving environmental sustainability. Keywords: groundwater, biopores, conservation, environment